An Action Research on Metacognitive Strategies to Teach Listening - Ni'matu Tasriyah (Bandar Lampung University (UBL), 2013)
AbstractWhile listening skill is an important skill for language learners, many students claim that this is the most difficult skill to master. Thus the teachers should help learners to master the listening skills. Metacognitive strategy is one of the solutions and how to teach listening, so that students can learn how to listen and not just what to listen for. Many research showed that metacognitive strategies can improve students’ listening. Thus, the purpose of this action research project was to help teachers in the teaching listening within the metacognitive strategies. The issue was do students enjoy their listening activity in their class, and what is the strategy to attract students enjoying the listening activity I their class. The research was conducted in a language training center in a private university in Jogjakarta, Indonesia. This action research was conducted in three steps. First, the students were surveyed by giving them questionnaire of listening activities donein their class. Students were, then, introduced to the listening activities by applying metacognitive strategies. In the process of listening activity students were taught by using framework on the listening activity. Having taught by those strategies, students were given the second questionnaire to compare which one is a better strategy for them to learn how to listen. By having these comparisons researcher concluded that students enjoy the listening activities using metacognitive strategy.